2018
DOI: 10.3168/jds.2018-14584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia fiber expansion on the available energy content of wheat straw fed to lactating cattle and buffalo in India

Abstract: The seasonal lack of availability of lush green forages can force dairy farmers in developing nations to rely on crop residues such as wheat and rice straw as the major feed source. We tested whether ammonia fiber expansion (AFEX) treatment of wheat straw would increase the energy available to Murrah buffalo and Karan-Fries cattle consuming 70% of their diet as wheat straw in India. Forty lactating animals of each species were blocked by parity and days in milk and randomly assigned to 1 of 4 treatment diets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Feeding trials with lactating dairy cows using AFEX-treated rice straw have shown adequate intake and no adverse health effects with the treated material (Weimer et al, 2003;Blummel et al, 2014). Recently, Mor et al (2018) reported improved nutrient digestibility (DM, OM, CP, NDF, and ADF) of AFEXtreated wheat straw for lactating buffalo and cattle, underscoring its commercial potential as an alternative to high-quality forages or grains. However, acetamide, a co-product of the AFEX treatment produced during cleavage of acetyl groups from hemicellulose (Weimer et al, 1986), is not volatile, rather it can remain with the treated biomass thereby increasing its N content (Bals et al, 2011).…”
Section: Alkali Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding trials with lactating dairy cows using AFEX-treated rice straw have shown adequate intake and no adverse health effects with the treated material (Weimer et al, 2003;Blummel et al, 2014). Recently, Mor et al (2018) reported improved nutrient digestibility (DM, OM, CP, NDF, and ADF) of AFEXtreated wheat straw for lactating buffalo and cattle, underscoring its commercial potential as an alternative to high-quality forages or grains. However, acetamide, a co-product of the AFEX treatment produced during cleavage of acetyl groups from hemicellulose (Weimer et al, 1986), is not volatile, rather it can remain with the treated biomass thereby increasing its N content (Bals et al, 2011).…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…Nevertheless, research on the effects and fate of residual acetamide in cattle fed AFEX-treated forages are needed to ensure that meat and milk are not contaminated. Recent animal trials have not reported adverse health effects (Blummel et al, 2014;Griffith et al, 2016;Mor et al, 2018). The main advantages of AFEX treatment over traditional ammoniation method include safety, as the pellets generated are benign, ease of transport due to density of the pellets, and recycling of the ammonia.…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…Details of these trials can be found in Mor et al. 9 Animals were housed in individual pens and fed ad libitum with 10 animals per treatment. In both trials animals were on a control diet for 3 weeks before transitioning to the treatment diet using AFEX-treated wheat straw pellets.…”
Section: Methodsmentioning
confidence: 99%
“…5 Ammoniation makes the cellulosic sugar polymers in crop residues more accessible to hydrolytic enzymes and also increases the inorganic nitrogen content, which result in increased digestibility of the crop residues in vitro 68 and in vivo. 9…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biofuels feedstock, AFEX‐treated crop residues have been fed to ruminant animals such as sheep, goats, cattle, and buffalo (Mor et al, ; Mor et al, ). The opportunity to utilize AFEX‐treated crop residues in both biofuel feedstock and cattle feed applications provides an advantage for regional AFEX processing centers and reduces the market risks associated with a single‐use application.…”
Section: Introductionmentioning
confidence: 99%